2014
DOI: 10.1183/09031936.00018414
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled antibiotics for stable non-cystic fibrosis bronchiectasis: a systematic review

Abstract: We conducted a meta-analysis of randomised trials to evaluate the efficacy and safety of inhaled antibiotics in patients with stable non-cystic fibrosis (CF) bronchiectasis.We searched the Cochrane Airways Group Register of Trials from inception until March 2014. 12 trials with 1264 adult patients were included, of which five were unpublished studies. Eight trials on 590 patients contributed data to the meta-analysis. Amikacin, aztreonam, ciprofloxacin, gentamicin, colistin or tobramycin were used for 4 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
0
14

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(131 citation statements)
references
References 31 publications
4
113
0
14
Order By: Relevance
“…However, the use of long-term inhaled antibiotics was associated with a higher risk of wheeze (odds ratio of 6.7) and bronchospasm (odds ratio of 2.8). Similar results were previously reported by Brodt et al, 26 suggesting that inhaled antibiotics may provide an effective suppressive antibiotic therapy. However, in contrast, they concluded that inhaled antibiotics have an acceptable profile for adult subjects with NCFB and chronic bronchial infection.…”
Section: Non-cystic Fibrosis Bronchiectasissupporting
confidence: 91%
See 1 more Smart Citation
“…However, the use of long-term inhaled antibiotics was associated with a higher risk of wheeze (odds ratio of 6.7) and bronchospasm (odds ratio of 2.8). Similar results were previously reported by Brodt et al, 26 suggesting that inhaled antibiotics may provide an effective suppressive antibiotic therapy. However, in contrast, they concluded that inhaled antibiotics have an acceptable profile for adult subjects with NCFB and chronic bronchial infection.…”
Section: Non-cystic Fibrosis Bronchiectasissupporting
confidence: 91%
“…24 We discuss the most relevant literature regarding the clinical application of aerosolized antibiotics for patients with CF, NCFB, and VAP infected with difficult-to-treat pathogens. 4,10,[25][26][27][28][29] …”
Section: Clinical Indications For Aerosolized Antibioticsmentioning
confidence: 99%
“…Despite heterogeneity in the testing methodology, the metaanalysis did not show a statistically significant difference in the emergence of bacterial resistance in the inhalation treatment group compared to the controls. This meta-analysis lends some support to the use of inhaled antibiotics for the treatment of chronic bacterial infections in the airways of patients with stable non-CF bronchiectasis (230). There was significant heterogeneity in this analysis, especially surrounding the duration of inhaled therapy.…”
Section: Non-cf Bronchiectasismentioning
confidence: 70%
“…In the primary care setting, once a specific type of ACT has been selected, the patients should be questioned about the regular use of this therapy and encouraged to be as compliant as possible. Chronic use of antibiotics, both oral and inhaled, has been used as suppressive therapy in selected patients with additional improvements in exacerbation rates, symptoms scores and quality of life markers 76, 77. These therapies should be carefully tailored based on the extent of the disease, daily symptoms and culture results.…”
Section: Diagnostic Approachmentioning
confidence: 99%